The Effect of Ibn Qayyim Al-Gauziyah's Thought on the Changing Paradigm of Islamic Law - Abdul Rahim; Misbahuddin; Kurniati; Rafi Pradipa (al-Afkar, Journal For Islamic Studies, 2023)
Changing the law is a necessity in this life. This work is here to explore the influence of Ibn Qayyum al-Gauziyah's thoughts on one of the theories of legal change. Ibn Qayyim al-Jauziyah in his legal thinking provides the widest possible space for the door of ijtihad in responding to change as a reality that cannot be avoided. Qualitative research methods using literature research while the analysis knife used is by analyzing information that has been collected from library data and social theory, or what is called the doctrinal-deductive method. The results of the discussion are that the legal change paradigm method is inseparable from the factors of the era, place, situation, intention and custom. Ibn Qayyim al-Gauziyah's theory of legal change is a concept of renewing Islamic legal thought. This means that Islamic law is a law that is dynamic, responsive and adaptable to demands for change. The implication of al-Jauziyah's theory of legal changes to society is in the context of achieving universal benefit in society as the purpose of the law itself.